2019
DOI: 10.1166/jbn.2019.2866
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of High Mobility Group Box-1 siRNA Using Brain-Targeting Exosomes for Ischemic Stroke Therapy

Abstract: Ischemic strokes are caused by decreased blood flow into the brain, due to narrowed cerebral arteries. In the ischemic brain, high-mobility group box 1 (HMGB1) is released into extracellular spaces and induces inflammatory reactions. In this study, HMGB1 small interfering RNA (siRNA) was delivered into ischemic brains by intravenous administration using rabies virus glycoprotein (RVG) peptide-decorated exosomes. A fusion protein of RVG and Lamp2b was expressed in 293T cells. Since Lamp2b is an exosome membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…In another study, HMGB1-siRNA was loaded into rabies virus glycoprotein (RVG) peptide-decorated exosomes (RVG-Exo) by electroporation and then delivered into the ischemic brain by intravenous injection in an MCAO model. The authors found a more efficient decrease in HMGB1 levels, TNF-α levels, apoptosis in the brain, and infarct volume in the RVG-Exo/HMGB1-siRNA group compared to that in the unmodified exosomes/HMGB1-siRNA group, indicating that RVG-Exo with HMGB1-siRNA may represent a novel therapeutic system for ischemic stroke treatment (Kim et al, 2019a). These findings further provide evidence of a new mechanism of dynamic crosstalk between HMGB1 and cerebral ischemia.…”
Section: Rna Interferencementioning
confidence: 81%
“…In another study, HMGB1-siRNA was loaded into rabies virus glycoprotein (RVG) peptide-decorated exosomes (RVG-Exo) by electroporation and then delivered into the ischemic brain by intravenous injection in an MCAO model. The authors found a more efficient decrease in HMGB1 levels, TNF-α levels, apoptosis in the brain, and infarct volume in the RVG-Exo/HMGB1-siRNA group compared to that in the unmodified exosomes/HMGB1-siRNA group, indicating that RVG-Exo with HMGB1-siRNA may represent a novel therapeutic system for ischemic stroke treatment (Kim et al, 2019a). These findings further provide evidence of a new mechanism of dynamic crosstalk between HMGB1 and cerebral ischemia.…”
Section: Rna Interferencementioning
confidence: 81%
“…To test if serum-derived exosomes are up taken by neural cells, we incubated neuronally differentiated N2a cells, a mouse neuroblastoma cell line, with exosomes labeled with the fluorescent membrane-binding dye PKH67. N2a cells were used as an in vitro model since neuroblastoma cells are an established model for neuronal uptake and biological activity of exosomes [33,36]. Key results were then confirmed using primary cultured neurons.…”
Section: Astrosomes Are Taken Up By Neural Cells and Transport Aβ Andmentioning
confidence: 97%
“…The transfection of donor cells can create EVs with specific peptides within their membrane. Rabies virus glycoprotein (RVG)-derived peptide, which binds p75 neurotrophin receptor, was conjugated to EVs, and then siRNA was loaded through electroporation [1,121,122]. Chen et al conjugated klotho protein to EVs, which binds circulating endothelial progenitor cells (EPCs).…”
Section: Sirnamentioning
confidence: 99%